2017
DOI: 10.1021/acs.jpca.7b05209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Rate of Thermal Decomposition of Hexachlorocyclopentadiene and Its Importance in PCDD/F Formation from the Combustion of Cyclodiene Pesticides

Abstract: Thermal decomposition of hexachlorocyclopentadiene (HCCP) has been studied in inert gas and under oxidative conditions in a silica flow reactor at a residence time of 5.0 s between 690 and 923 K and 1 atm pressure. Pyrolysis was initiated by Cl bond fission to form pentachlorocyclopentadienyl radical; two such radicals then combined to undergo a series of intramolecular rearrangements and Cl fissions, producing principally octachloronaphthalene (8ClNP) and Cl. This process has been studied by quantum chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…At 600 K, IM3 would possess a peak thermal energy of 240 kJ mol –1 such that IM3 would not be stabilized and would possess more than sufficient energy to surmount the small barrier to form IM4. Kislov and Mabel used similar reasoning in developing a kinetic model for combination of two cyclopentadienyl radicals and we have been able to develop an analogous kinetic model for combination of two pentachlorocyclopentadienyl radicals with a similar assumption. We have allowed a small barrier of 21 kJ mol –1 for the chemically activated combination of two TCpyoxy radicals to form IM4 + Cl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 600 K, IM3 would possess a peak thermal energy of 240 kJ mol –1 such that IM3 would not be stabilized and would possess more than sufficient energy to surmount the small barrier to form IM4. Kislov and Mabel used similar reasoning in developing a kinetic model for combination of two cyclopentadienyl radicals and we have been able to develop an analogous kinetic model for combination of two pentachlorocyclopentadienyl radicals with a similar assumption. We have allowed a small barrier of 21 kJ mol –1 for the chemically activated combination of two TCpyoxy radicals to form IM4 + Cl.…”
Section: Resultsmentioning
confidence: 99%
“…Improved energy calculations have been carried out at the M06-2X/GTLarge//M06-2 X /6-31+G­(d,p) level of theory. We have chosen to use this method because of its previous success in the computation of large polychlorinated molecules such as endosulfan, dieldrin, hexachlorocyclopentadiene and their products. Rate constants at the high pressure limit for unimolecular reactions have been calculated by the ChemRate program using thermochemical parameters obtained from the quantum chemical computations.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Quantum chemistry technique as a method has been developed to assist in the structural modulation for multiple catalysts. For example, N K Dharmarathne et al 12 investigated the thermal decomposition of hexachlorocyclopentadiene (HCCP) in a uidized bed reactor under the inert and oxidizing conditions, respectively. It has been found that at high O-2 levels ( > similar to 10%), the decomposition rate of HCCP as well as the yields of 8ClNP and HCB decreased, which con rmed that quantum chemistry technique can be used to simulate and calculate reactions between gaseous molecules.…”
Section: Introductionmentioning
confidence: 99%